# algebra

posted by
**Marissa**
.

1)Write the expression 9n^6+7n^3-6 in quadratic form,if possible

A.9(n^3)^3+7n^3-6

B.9(n^2)^3+7(n^2)-6

C.9(n^3)^2+7(n^3)-6

D.not possible

I'm thinking C on this one but im not sure

2)solve b^4+2b^2-24=0

A.-2,-square root of 6,square root of 6,2

B.-square root of 6,2,2i,i square root of 6

C.2,2,-isquare root of 6

D.-2i,2i,- square root of 6,square root of 6

3)If f(x)= x^2+1 and g(x)= x-2,find f[g(x)]

A.x^2-4x+5

B.x^2-1

C.x^2-3

D.x^3-2x^2+x-2

my answer is B

4)Find the inverse of f(x)= 2x-7

=f-1(x)= x+7/2

5)Determine which pair of functions are inverses:

A.f(x)= 3x-1;g(x)= 1/3x-1

B.f(x)= 2x-5;g(x)= x+5/2

C.f(x)= 2x+2;g(x)= 2x-2

D.f(x)= 3x-8;g(x)= 1/3x+8

my answer is D or B

2.) C

3.)A

f[g(x)] = (x-2)^2 + 1

= x^2 -4x +5

4.)correct

5.) B

Follow the same procedure you did for number 4

1. C is right

2. b^4 + 2b^2 - 24 = 0

b^4 + 2b^2 = 24

b^4 + 2b^2 **+ 1 ** = 24 **+ 1 **

(b^2 + 1)^2 = 25

b^2 + 1 = ± 5

b^2 = 4 or b^2 = -6

b= ±2 or b= ±i√6

3. I got A

f[g(x)]

= f(x-2)

= (x-2)^2 + 1

= x^2 - 4x + 4 + 1

= x^2 - 4x + 5

4. ok if you include brackets as in (x+7)/2

5 ok if you include brackets as in (x+5)/2 and (1/3)(x+8)